Kepemimpinan Kepala Madrasah dalam Mengimplementasikan Kurikulum Merdeka - Junaidi, Junaidi; Idrus, Ali Jadid Al; Bahtiar, Bahtiar (Jurnal Manajemen & Budaya, 2024)
The aims of this research are: 1) to analyze the policy of the madrasah principal in supporting the implementation of the independent curriculum, 2) to determine the process of implementing the independent learning curriculum and 3) to determine the implications of the madrasah principal in implementing the curriculum independently. This research uses a qualitative approach with an emphasis on evaluating descriptive data. Data collection was obtained using interviews, observation and documentation methods. The research results show that 1) the madrasa head's policy in supporting the implementation of the independent learning curriculum includes concrete steps such as developing teacher training programs, resource allocation, forming a curriculum implementation team, and efforts to facilitate cultural change in madrasas. 2) The process of implementing the independent curriculum is running well according to established procedures and the madrasa head is directly involved in the monitoring and evaluation process to measure success and ensure this curriculum runs effectively and efficiently. 3) The implications of madrasa heads in implementing an independent curriculum are very important to ensure the success and effectiveness of an education system based on freedom and creativity